Ode to positive constructive daydreaming - McMillan, Rebecca; Kaufman, Scott B.; Singer, Jerome L. (Frontiers in Psychology, 2013)
Nearly 60 years ago, Jerome L. Singer launched a groundbreaking research program into daydreaming (Singer, 1955, 1975, 2008) that presaged and laid the foundation for virtually every major strand of mind wandering research active today (Klinger, 1999; Antrobus 1999; Klinger, 2009). Here we review Singer’s enormous contribution to the field, which includes insights, methodologies, and tools still in use today, and trace his enduring legacy as revealed in the recent proliferation of mind wandering studies. We then turn to the central theme in Singer’s work, the adaptive nature of Positive Constructive Daydreaming, which was a revolutionary idea when Singer began his work in the 1950s and remains underreported today. Last, we propose a new approach to answering the enduring question: Why does mind wandering persist and occupy so much of our time, as much as 50% of our waking time according to some estimates, if it is as costly as most studies suggest?